A metal-organic framework (MOF)-based temperature swing adsorption cycle for postcombustion CO2 capture from wet flue gas. (15th March 2022) - Peh, Shing Bo; Farooq, Shamsuzzaman; Zhao, Dan
Highlights: Two single-stage cycles of a TSA process operated on a MOF adsorbent, UTSA-16, are proposed for CO2 capture and concentration from a wet flue gas. Cycles can meet 95% purity-90% recovery targets at various concentration levels without pre-drying or a desiccant pre-layer. The TSA process overcomes deep vacuum limitations of current low-temperature cycles despite the presence of water. Abstract: We report a simulation-based feasibility study of a single-stage temperature swing adsorption (TSA) process operated on a metal–organic framework (MOF) adsorbent, UTSA-16, for CO2 capture and concentration from a wet flue gas without pre-drying or a desiccant pre-layer. Two cycles comprising four and five-steps are compared. A non-isothermal and non-isobaric in-house simulator including suitably modelled equilibrium and kinetics of H2 O-CO2 -N2 ternary system is used to investigate the cyclic processes. The variables investigated are moisture-saturated flue gas at two feed and three regeneration temperatures. Both TSA cycles can meet 95% purity-90% recovery targets for postcombustion streams representative of wet flue gas from a coal-fired power plant (after SOx /NOx removal). The maximum productivity attained is 91.8 kg CO2 m −3 adsorber h −1 for 15% CO2, 82 % N2, and 3% H2 O feed at 25 °C (i.e., 95% relative humidity) operated on a five-step cycle and regenerated at 150 °C.